Pemahaman Mahasiswa Jurusan Akuntansi Atas Penerapan International Financial Reporting Standard dalam Menghadapi Masyarakat Ekonomi Asean - Gayatri, Gayatri; Widanaputra, A.A G.P; Suprasto H., Bambang (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016)DO - 10.24843/JIAB.2016.v11.i01.p02, 2016)
The aims of this research is to determine the accounting student’s of  understanding the application of International Financial Reporting Standardin the Asean Economic Community. Data collected through questionnaires. The sampling technique is done by purposive sampling that students of the accounting department term IV and V of the school year 2014/2015 at the Faculty of Economics and Business, Udayana University. The analysis in this study uses procentage descriptive method. This research found that students from the accounting department are well understand the development of the profession, opportunities, and chalenges facing the accounting profession in the Asean Economic Community. Keywords: Accounting, IFRS, ASEAN economic community
Keywords: accounting, IFRS, ASEAN Economic Community